Vegetable beverages prepared with brazilians nuts: a systematic review (Research, Society and Development, 2023)
Nowadays, plant-based beverages have somehow become a lifestyle tool, consumed by many not just because of dietary issues, but also for individual beliefs as well. Brazil, due to its wide biodiversity, has a high potential to play an active role in the global scenario in the production of these beverages. The aim of this work was to identify the main scientific works about Brazilians nuts plant-based beverages, in order to highlight which plants has been used, how these beverages has been prepared and what is their nutritional, biochemical, antioxidant and sensory potential. The study is a systematic review, using data available in different bases of CAPES journals (Scopus, Web of Science, Pubmed, Embase and Scielo), following the steps: formulation of the question, data collection (identification), selection (exclusion), definition of eligibility characteristics and analysis of selected evidence. 3,598 articles were identified, where through the selection process 12 documents were approved. These beverages have an intermediate sensorial acceptance and a high nutritional potential. Currently, in Brazil there are ranges of nuts options that can still be explored. There are few scientific studies related to the subject, however, through research in different databases, a gradual increase have been noted by the years. These scientific experiments are important to verify and/or verify the potential of these almonds/nuts originating in Brazil in the preparation of plant-based beverages, since the demand for healthy alternatives to animal-based products also grows every day.